In Vitro Screening for Antimicrobial Activity of Some Medicinal Plant Seed Extracts - Gomaa, Emad El Din G.; Esmaiel, Naglaa M.; Salem, Mohamed Z.M.; Gomaa, Sara E. (International Journal of Biotechnology for Wellness Industries, 2016)
Phytochemical screening (saponins, tannins, steroids, alkaloids, flavonoids, phenols and glycosides) of four medicinal plant seeds (Jatropha curcas, Simmondsia chinensis (Jojoba), Moringa oleifera and Datura metel) extracted by aqueous, ethanol and Folch solvents, were examined for their antimicrobial activity against three types of plant pathogenic fungi namely; Botrytis cinerea, Fusarium oxysporum and Rhizoctonia solani, in addition to four types of bacteria, namely; Bacillus cereus, Staphylococcus aureus, Ralstonia solanacearum and Pesudomonas aeruginosa using disc diffusion paper. Results revealed that different concentrations of aqueous extracts were more effective against bacterial activity compared to fungal activity, except for D. metel aqueous extract which showed no antifungal effect and very weak effect on only two of the tested bacteria. B. cereus was more sensitive to J. curcas aqueous extract, while P. aeruginosa was more sensitive to S. chinensis and M. oleifera aqueous extracts. On the other hand, results showed that J. curcas and M. oleifera ethanol extracts were more effective on Staph. aureus growth, while S. chinensis and D. metel did not have any effect on any of the fungi or bacteria under study. The evaluation of the antifungal and antibacterial effect did not confirm the broad spectrum of S. chinensis Folch extract, while M. oleifera and D. metel were more effective on reducing R. solani growth. Also F. oxysporum was affected by J. curcas Folch extract only at high concentrations. These findings support that the traditional use of the plant extracts in the treatment of different infections caused by pathogenic microbes is valuable and should be taken in consideration.